2006
DOI: 10.1002/da.20155
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician–gynecologists and self-identified depression: personal and clinical

Abstract: A survey was designed to explore the effect of obstetrician-gynecologists' subjective awareness of depression in themselves and close family/friends on screening patients for depression and on assessing and treating depression in three scenarios describing hypothetical patients during the adolescence, postpartum, and perimenopausal periods. Questionnaires were mailed to 397 members of the American College of Obstetricians and Gynecologists (ACOG) who participate in the Collaborative Ambulatory Research Network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In an accompanying survey, when asked what the best way to treat possibly depressed hypothetical patients would be, we found that respondents who had samples of antidepressants available were far more likely to indicate treatment with antidepressants than were those who did not have samples available. 23 This suggests an association between sample availability and increased prescribing. Alternative explanations are possible-for example, doctors who are more likely to prescribe may be more likely to keep samples available.…”
Section: Discussionmentioning
confidence: 99%
“…In an accompanying survey, when asked what the best way to treat possibly depressed hypothetical patients would be, we found that respondents who had samples of antidepressants available were far more likely to indicate treatment with antidepressants than were those who did not have samples available. 23 This suggests an association between sample availability and increased prescribing. Alternative explanations are possible-for example, doctors who are more likely to prescribe may be more likely to keep samples available.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese obstetricians work about 49 hours for women and 55 hours for men [22]. A study from the United States reported that a third of the members of the American College of Obstetricians and Gynecologists had depression [23]. Of the obstetricians who participated in this study, 27.3% had suffered from depression at some time, 34.3% had had depression the year before, and 16.5% of obstetricians were depressed at the time of the study.…”
Section: Resultsmentioning
confidence: 77%
“…For example, Coleman and colleagues [5] found that almost 30% of ob-gyns incorrectly diagnosed a hypothetical patient vignette with MDD, with about half of those who wrongly diagnosed the patient then prescribing an antidepressant. Further, though 72.6% of ob-gyns see adolescent patients at least monthly [6] and prevalence rates of MDD in this population are reported just above 11% [7], as little as 34% of ob-gyns have reported routinely screening for MDD in the adolescent population [8].…”
Section: Introductionmentioning
confidence: 87%